Mortality from diabetes mellitus and its impact on life expectancy at 60 years of age in Mexico - María Guadalupe Vega-López; Guillermo Julián González-Pérez
ABSTRACT OBJECTIVES To analyze the behavior of mortality from diabetes mellitus (DM) for both sexes in Mexico from 1998 to 2018, and its impact on life expectancy (LE) from 60 to 85 years of age in the three-year periods 1998-2000 and 2016-2018, compared with other causes of death, as well as to determine the loss of years of life expectancy associated with DM in each three-year period. METHODS The current study is observational and descriptive. Age-adjusted rates of mortality from DM were calculated for each sex from 1998 to 2018. Sex-specific life tables were constructed for 1998-2000 and 2016-2018, and both LE between 60 and 85 years, and years of life expectancy lost (YLELL) due to DM and selected causes between both ages were calculated. RESULTS Between 1998 and 2018, the adjusted DM-resulting male mortality rate grew 55% in the population aged 60 and over, while the female mortality rate grew 20%. Between 1998-2000 and 2016-2018, male LE for 60-85 age group decreased 0.22 years, while female LE increased 0.24. In 2016-2018, DM was responsible for 1.30 YLEL among men of 60 to 85 years (19% of the total YLEL), and 1.24 YLEL for women (24% of the total), more than the other causes analyzed. CONCLUSIONS The increase in mortality from DM has substantially contributed both to reduce LE of older adult men, and to slow the increase of LE among women aged 60 years and older so far this century. Thus, preventive policies should be implemented since early ages to reduce the high levels of overweight and obesity in the country and, therefore, the significant population ratio suffering from DM.